(untitled) (Journal of Event, Tourism and Hospitality Studies, 2021)
The high demand from customers for quality services and competitive environment in the fast food industry give rise to the need to improve customers’ satisfaction that will increase the restaurant’s revenue. The objective of this study is to investigate the factors effecting customers’ satisfaction in fast food restaurants namely the price, service quality, and food quality of fast food restaurants in Arau, Perlis. The fast food restaurants selected for this study are Marry Brown, KFC, Pizza Hut and Domino’s Pizza. A quantitative method was applied using online questionnaire to collect data from customers. The respondents consisted of customers who had experienced purchasing at these fast food restaurants. The findings of the study revealed that there is a significant relationship between customers’ satisfaction and the price of the foods. However, the study indicated insignificant relationships between food quality, service quality of fast food businesses and customers’ satisfaction. For future studies, it is recommended that the study area is expanded to involve various samples of the population, for broader results. To obtain more precise and reliable results, a similar study considering other factors that influence customer satisfaction in fast food restaurants could be added as variables.